2020
DOI: 10.1177/1474515120927121
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, recovery and psychological wellbeing one to five years after heart transplantation: a Swedish cross-sectional study

Abstract: Background Self-efficacy refers to a person´s confidence in carrying out treatment-related activities and constitutes the foundation of self-management as well as long-term follow-up after heart transplantation. Exploring the heart recipients´ experiences by means of self-report instruments provides healthcare professionals with valuable information on how to supply self-management support after heart transplantation. Aims The aim was to explore self-efficacy in relation to the self-reported level of recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…Pretransplant MCS treatment seems to have impact on experiences post-transplant. It has previously been shown that HTRs who underwent MCS treatment pretransplant had lower self-efficacy than those without such treatment [33] and the present study reveals that this group also reports a higher degree of fatigue. This is an interesting and important finding, as the transplant candidates who underwent MCS were probably in better physical condition at the time of the transplantation than those without MCS.…”
Section: Discussionsupporting
confidence: 65%
“…Pretransplant MCS treatment seems to have impact on experiences post-transplant. It has previously been shown that HTRs who underwent MCS treatment pretransplant had lower self-efficacy than those without such treatment [33] and the present study reveals that this group also reports a higher degree of fatigue. This is an interesting and important finding, as the transplant candidates who underwent MCS were probably in better physical condition at the time of the transplantation than those without MCS.…”
Section: Discussionsupporting
confidence: 65%
“…Readiness for discharge correlates strongly with coping at home in this study. These findings illustrate that disease-specific education for parents should target their sense of self-efficacy [ 22 ] and internal control at least as much as actual disease-related skills. In the knowledge tests, questions targeting “need to do” topics such as vaccinations, or taking of immunosuppressive education, had higher response rates than questions regarding theorectical background knowledge.…”
Section: Discussionmentioning
confidence: 92%
“…In the context of our secondary analysis, we identified 41 records from a total pool of included 742 scoping review records contained definitions. Screening of these records resulted in eight “original” definitions [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Sixty three records were identified through secondary sources [ 20 , 21 , 23 , 25 , 26 , 28 , 30 , 31 , 33 , 34 , 35 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
“…A single definition focused on an aspect of SM medication adherence [ 44 ], and the remainder focused on all aspects. Definitions focused on one or multiple transplant organ types: heart [ 46 , 49 , 50 ], liver [ 45 , 48 , 49 ], kidney [ 44 , 45 , 49 , 51 ], pancreas [ 49 ], and lung [ 49 ] ( Supplementary File S2 ). Amongst the definition publications, seven of the eight are quantitative studies, with one qualitative [ 51 ].…”
Section: Resultsmentioning
confidence: 99%